2019
DOI: 10.1002/adma.201904197
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Ferroptosis Inducers for Cancer Therapy

Abstract: Ferroptosis is a newly discovered form of regulated cell death that is the nexus between metabolism, redox biology, and human health. Emerging evidence shows the potential of triggering ferroptosis for cancer therapy, particularly for eradicating aggressive malignancies that are resistant to traditional therapies. Recently, there has been a great deal of effort to design and develop anticancer drugs based on ferroptosis induction. Recent advances of ferroptosis‐inducing agents at the intersection of chemistry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
878
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,175 publications
(941 citation statements)
references
References 153 publications
6
878
1
1
Order By: Relevance
“…Second, FIN56 binds to the enzyme squalene synthase, which leads to the depletion of endogenous antioxidant coenzyme Q10 (COQ10). This process enhances cell sensitivity to FIN56-induced ferroptosis 8 . The final category includes FINO2, an organic peroxide with many features in common with artemisinin, which causes ferroptosis due to a combined effect of the direct oxidation of labile iron and the inactivation of GPX4 8 .…”
Section: An Overview Of Ferroptosismentioning
confidence: 94%
See 1 more Smart Citation
“…Second, FIN56 binds to the enzyme squalene synthase, which leads to the depletion of endogenous antioxidant coenzyme Q10 (COQ10). This process enhances cell sensitivity to FIN56-induced ferroptosis 8 . The final category includes FINO2, an organic peroxide with many features in common with artemisinin, which causes ferroptosis due to a combined effect of the direct oxidation of labile iron and the inactivation of GPX4 8 .…”
Section: An Overview Of Ferroptosismentioning
confidence: 94%
“…This process enhances cell sensitivity to FIN56-induced ferroptosis 8 . The final category includes FINO2, an organic peroxide with many features in common with artemisinin, which causes ferroptosis due to a combined effect of the direct oxidation of labile iron and the inactivation of GPX4 8 . With the deepening of research on the mechanism of ferroptosis, many specific inhibitors of ferroptosis, such as ferrostatin-1 (Fer-1), liproxstatin-1 and vitamin E, have been found, in addition to iron chelators.…”
Section: An Overview Of Ferroptosismentioning
confidence: 94%
“…One of the most important hallmarks of cancer is the efficient evasion of regulated cell death. Recently, ferroptosis, a new, yet potentially evolutionary ancient type of regulated necrosis which is triggered upon collapse of a lipid radical-specific antioxidant defence system was described [15] (recently also reviewed [16][17][18][19][20]). Whereas apoptosis, necroptosis and pyroptosis are all either directly dependent on caspases or inhibited by their activity (reviewed in-depth elsewhere [21]), ferroptosis seems to have evolved separately with, as of yet, very little known direct molecular cross-talk to other pathways of regulated cell death [21].…”
Section: Introductionmentioning
confidence: 99%
“…Selective induction of cancer cell death is the most effective therapy method for tumor [31]. Several literatures reported that ferroptosis, a common selective induction cell death, plays pivotal role in the process of tumorigenesis [32,33]. However, the systematic analysis of prostate cancer has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%